2016
DOI: 10.1111/jvp.12366
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of minocycline in foals and adult horses

Abstract: The objective of this study was to compare the pharmacokinetics of minocycline in foals vs. adult horses. Minocycline was administered to six healthy 6- to 9-week-old foals and six adult horses at a dose of 4 mg/kg intragastrically (IG) and 2 mg/kg intravenously (i.v.) in a cross-over design. Five additional oral doses were administered at 12-h intervals in foals. A microbiologic assay was used to measure minocycline concentration in plasma, urine, synovial fluid, and cerebrospinal fluid (CSF). Liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
2
17
4
Order By: Relevance
“…Alternately, had plasma concentrations been obtained, the variability may be more clearly defined as due to GI and liver absorption. Previous studies investigating the difference between intravenous and oral administration have shown reduced bioavailability when the drug is given orally in adult horses versus foals . Furthermore, despite identical dosing and ad libitum feeding regimes, the concentrations in Giguere et al .…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Alternately, had plasma concentrations been obtained, the variability may be more clearly defined as due to GI and liver absorption. Previous studies investigating the difference between intravenous and oral administration have shown reduced bioavailability when the drug is given orally in adult horses versus foals . Furthermore, despite identical dosing and ad libitum feeding regimes, the concentrations in Giguere et al .…”
Section: Discussioncontrasting
confidence: 70%
“…Furthermore, despite identical dosing and ad libitum feeding regimes, the concentrations in Giguere et al . were higher than that reported in Schnabel et al . The reason for this discrepancy was concluded to be unknown.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While significant differences in T max were not identified between oral‐fasted and oral‐fed groups, the T max of 5 hr in oral‐fed versus 2 hr in oral‐fasted horses suggests that hay might delay drug absorption. In contrast to fasted bioavailability (38.6%), oral‐fed bioavailability (15.7%) was much lower than previously reported for minocycline in adult horses (Echeverria et al., ; Giguère et al., ; Schnabel et al., ). Previous minocycline studies reported intragastric administration with various feeding protocols: ad libitum grass hay with pelleted feed twice daily (Schnabel et al., ); ad libitum grass hay (Giguère et al., ); or two flakes of grass hay twice daily (Echeverria et al., ).…”
Section: Mean ± Sd Values For Precision and Accuracy Of Lc/ms/ms For contrasting
confidence: 55%
“…In contrast to fasted bioavailability (38.6%), oral-fed bioavailability (15.7%) was much lower than previously reported for minocycline in adult horses (Echeverria et T A B L E 2 Plasma pharmacokinetic variables (mean ± SD unless otherwise specified) after IV (2.2 mg/kg) or oral (4.0 mg/kg) administration of minocycline to six adult horses. Horses treated orally were either fasted overnight and fed hay 2 hr after drug administration (fasted) or fed hay prior to drug administration (fed) 2016; Giguère et al, 2016;Schnabel et al, 2012). Previous minocycline studies reported intragastric administration with various feeding protocols: ad libitum grass hay with pelleted feed twice daily (Schnabel et al, 2012); ad libitum grass hay ; or two flakes of grass hay twice daily (Echeverria et al, 2016).…”
mentioning
confidence: 99%